Geomorphic Characteristics of WRC-1 Watershed, Chargarh River Basin, Central India: Possible Implications on Hydrogeological Status - Fuladi, A.; Deshmukh, M. S. (Journal of Scientific Research, 2023)
Every geomorphic feature has its own distinct impact on the static groundwater level(SWL), seasonal water table fluctuation(WTF) and yield of the wells. The aim of this study was to analyze the role of geomorphic features over the groundwater regime and its possible implications on hydrogeological status within WRC-1 watershed. The watershed is covered by the Deccan basalt lavaflows and Quaternary alluvium. The geomorphic units of study area are HDP, MDP, residual hill, valleyfills, scarp, pediment, pediplain, butte, alluvial plain and gullied land to identify the relationship between geomorphic units and corresponding hydrogeological status. The pre-monsoon SWL, WTF and yield of the open-dug wells are analyzed. The high groundwater level fluctuation is indicated by residual hill, plateau remnant, HDP, MDP, pediment as compared to pond, river, younger alluvial plain and pediplain. Pre-monsoon yield of dugwells in river older alluvium are comparatively high; butte, residual hill, pond, river, dam/reservoir and valley fill which are comparatively moderate to low. The overall findings indicate that seasonal WLF in the hard rock terrain(basalt) is high compared to soft rock formation(alluvium).The best suitable area identified is Pediplain which is categorized as very good groundwater prospectus zone with pre-monsoon SWL(5.8mbgl), WTF(3.1m) and yield of the well(108000liter/day) respectively.